Compounding a Base - Norda Essential Oil and Chemical Company (1950)
View of a chemist compounding a base from abyssinian civet, otto of rose from Bulgaria, and absolutes floral oil from Italy, France, and Palestine at the Norda Company plant in Boonton, New Jersey.
Keywords: Norda Essential Oil and Chemical Company; Essences and essential oils industry; Perfumes industry; Employees; Research, Industrial--Laboratories